Management of a Patient With Tetralogy of Fallot, Congenital Diaphragmatic Hernia, and Complete Left Lung Agenesis. Issue 1 (1st July 2016) - Labovsky, Kristen; Hoffman, George; Scott, John
Abstract : We describe the rare case of an infant with congenital diaphragmatic hernia, unilateral lung agenesis, and unpalliated single-ventricle physiology. Infants with congenital diaphragmatic hernia and parallel circulation are at risk for maldistribution of systemic and pulmonary blood flow. Optimal perioperative management should include an assessment of the ratio of pulmonary to systemic blood flow (Qp:Qs). Traditionally, arterial and systemic venous oxygen (SvO2 ) saturations are needed to calculate Qp:Qs. However, in this case, SvO2 measurement was not feasible. On the basis of a previously described relationship, we used 2-site near-infrared spectroscopy to calculate a near-infrared spectroscopy–derived SvO2, which was then used to estimate Qp:Qs and guide goal-directed interventions.